Converging and diverging pressures in PBB development: the experiences of Finland and Sweden. Issue 12 (2nd December 2018) - Grossi, Giuseppe; Mauro, Sara Giovanna; Vakkuri, Jarmo
ABSTRACT: This paper aims to provide institutional explanations for the development of performance-based budgeting (PBB). Particularly, we explore the tensions between converging and diverging pressures. By analysing PBB in two countries with significant experience with it, Finland and Sweden, the research explains why we observe only evolutionary changes in actual budgetary practices. Indeed, the introduction of this practice is part of a global reform process undertaken over decades by public sector organizations. Nevertheless, the countries still struggle with PBB and, despite global converging pressures, diverging pressures shape its development, challenging its implementation and use, and paving the way for evolutionary changes.